2021
DOI: 10.1093/clinchem/hvab249
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Kidney Function: A Two-Sample Mendelian Randomization Study

Abstract: Background Obesity and type 2 diabetes (T2D) are correlated risk factors for chronic kidney disease (CKD). Methods Using summary data from GIANT (Genetic Investigation of Anthropometric Traits), DIAGRAM (DIAbetes Genetics Replication And Meta-analysis), and CKDGen (CKD Genetics), we examined causality and directionality of the association between obesity and kidney function. Bidirectional 2-sample Mendelian randomization (MR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
0
31
2
Order By: Relevance
“…Obesity has been linked to increased risk for CKD according to multiple large‐scale meta‐analysis study 32,33 ; nevertheless, the risk appears to be directly correlated with metabolic syndrome parameters such as abdominal obesity, hypertriglyceridemia, hypertension and low HDL levels 34 . A meta‐analysis study conducted in 2017 over 630.677 participants with a mean follow‐up period of 6.8 years demonstrated that obesity with or without metabolic abnormalities has been associated with a decline in eGFR and risk of albuminuria, whereas, no such association has been recorded in overweight participants 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been linked to increased risk for CKD according to multiple large‐scale meta‐analysis study 32,33 ; nevertheless, the risk appears to be directly correlated with metabolic syndrome parameters such as abdominal obesity, hypertriglyceridemia, hypertension and low HDL levels 34 . A meta‐analysis study conducted in 2017 over 630.677 participants with a mean follow‐up period of 6.8 years demonstrated that obesity with or without metabolic abnormalities has been associated with a decline in eGFR and risk of albuminuria, whereas, no such association has been recorded in overweight participants 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is an established risk factor for hypertension, diabetes, CVD, and CKD. 8 , 9 , 10 , 11 , 12 Many studies have identified an increased risk of albuminuria with higher body mass index (BMI) in the general adult population. 13 , 14 , 15 Obesity begins in childhood, and childhood BMI predicts obesity and other long-term health outcomes in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the study design, causality between obesity metrics and eGFR can not be suggested. Kjaergaard et al used Mendelian Randomization method to estimate direct causal effect of BMI and WHR on kidney function [ 31 ]. Kjaergaard et al focused on the verification of causality between specific body composite factor and renal dysfunction, while our study conducted for finding best predictor among body composite metrics of kidney dysfunction.…”
Section: Discussionmentioning
confidence: 99%